Methods of sampling repairs industry are outsourcing - A. V. Shimokhin (Вестник СибАДИ, 2017)
This article identifies the main factors affecting the cost of repairing the machines. The technique allows to decide on the transfer of repair outsourcing, based on the classification of the equipment in the parameters: the complexity of the repair and the mean time to failure.As a result of the proposed algorithm determines the optimal selection of the number of repairs carried out by the company-outsourcer, in which the cost of maintenance and repair of equipment is minimal.